Prospects and directions of diversification of oilseed group crops - Valentyna Gamayunova; Lyubov Khonenko; Vira Mykolaichuk; Anna Kuvshinova (Наукові горизонти)
The purpose of the study was to examine the influence of technology elements on the yield and quality of oil from various varieties of oilseeds, in particular, sunflower, rapeseed, safflower, camelina, and brown mustard. The effectiveness of various agricultural techniques (types of fertilisers, protection systems, and agrotechnical measures) to improve the quality and quantity of these crops was evaluated. The study was conducted for three years on the basis of the educationalscientific-practical centre of Mykolaiv National Agrarian University. The methodology included conducting field experiments with various agronomic technologies, laboratory analysis of the obtained plant samples, and determining the oil content. According to the results, the use of an optimised nutrition system and a combined protection system increases the yield of sunflower seeds by 15%, the quality of oil by 10%, and the use of innovative elements for growing flax increases the oil content of seeds by 8%. For rapeseed, it was determined that the use of adopted nutrition and protection systems increases the yield by 20%. The mustard examination showed a substantial improvement in the crop’s resistance to diseases when using integrated plant protection. The findings confirmed the importance of choosing the optimal elements of the technology that contribute to improving the yield and quality of oilseeds. This issue is relevant since oilseeds occupy a substantial place in the agro-industrial complex. Increasing the efficiency of growing oilseeds not only provides stable profits for farmers but also has a positive impact on the food security of the country in general. Thus, the introduction of scientifically based agronomic measures is a critical factor for achieving sustainable development of the agricultural sector and diversification of oilseeds